2005
DOI: 10.1037/1064-1297.13.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Using Behavioral Theories of Choice to Predict Drinking Outcomes Following a Brief Intervention.

Abstract: Behavioral theories of choice predict that substance use is partly a function of the relative value of drugs in relation to other available reinforcers. This study evaluated this hypothesis in the context of predicting drinking outcomes following an alcohol abuse intervention. Participants (N ϭ 54, 69% female, 31% male) were college student heavy drinkers who completed a single-session motivational intervention. Students completed a baseline measure of substance-related and substance-free activity participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
203
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(222 citation statements)
references
References 55 publications
(88 reference statements)
15
203
4
Order By: Relevance
“…Other environmental factors may also infl uence changes in high-risk drinking over the summer. For example, students who live at home over the summer may have more free time and opportunity to enjoy substance-free alternatives to drinking (e.g., family activities, going to the pool or the beach, summer athletics), which may serve as a protective factor among heavy drinkers (Murphy et al, 2005). Regardless, the discrepancy in outcomes based on residence seems to indicate that living with a parent or guardian is effective in eliciting changes in college student drinking.…”
Section: Discussionmentioning
confidence: 84%
“…Other environmental factors may also infl uence changes in high-risk drinking over the summer. For example, students who live at home over the summer may have more free time and opportunity to enjoy substance-free alternatives to drinking (e.g., family activities, going to the pool or the beach, summer athletics), which may serve as a protective factor among heavy drinkers (Murphy et al, 2005). Regardless, the discrepancy in outcomes based on residence seems to indicate that living with a parent or guardian is effective in eliciting changes in college student drinking.…”
Section: Discussionmentioning
confidence: 84%
“…It has been proposed, for example, that university drug prevention programs might draw on developments in the use of extracurricular activities to bring about behavioural change (Polymerou, 2007). Studies have shown that increases in student activities are associated with decreases in drinking on campus (Murphy, Correia, Colby, & Vuchinich, 2005). Similar programs have been used in schools.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers have found that people who disregard the future and are motivated by immediate rewards (Rahman et al, 2001) are both more aggressive (Manuck et al, 1998) and consume more alcohol (Murphy et al, 2005) relative to controls. Perhaps supporters of winning or drawing teams experience such a disregard for the future; if so, aggression and planned alcohol consumption may not be causally associated but linked by the same underlying cognitive process (see also McMurran, 2003).…”
Section: Discussionmentioning
confidence: 99%